A Decision-making Model for Supplier Selection in Indian Pharmaceutical Organizations. (September 2019) - Ganguly, Anirban; Kumar, Chitresh; Chatterjee, Debdeep
Supplier selection is the process by which firms identify, evaluate and contract with suppliers. The supplier selection process deploys a tremendous amount of a firm's operational and financial resources and is considered as an important determinant of the success of its supply chain. In spite of being strategically important to organizations, the decision for supplier selection is often complex and unstructured. Furthermore, it is inherently a multi-criterion decision-making (MCDM) problem, which pertains to structuring and solving decision problems involving multiple criteria. The paper provides a framework to analyze and evaluate supplier selection in Indian pharmaceutical sector (IPS) using MCDM technique of fuzzy analytic hierarchy process. It intends to improve managerial decision-making in the IPS in developing a supplier selection strategy based on multi-criteria evaluation technique.